Model experimental of questionnaire for identification of possible individuals that present indications of vigorexia - Rodrigues, Jetro Bezerra (2012)
Objective: To propose a questionnaire that comes to identify possible upset related to the vigorexia, where the same can come to be more an evaluation instrument in the anamnese of the academy visitors. Materials and Methods: Proposition of a questionnaire for predisposition of vigorexia indications, being formulated ten objective subjects, attributing a punctuation specifies for each subject linking to the tied up themes to that upset. Results and Discussion: Through the revision of the related goods the vigorexia, was looked for to embrace artifices that were tied up to that upset with the prerogative of formulation of a questionnaire that can be a middle of verifying some predisposition type that takes the academy visitors they suffer it with that upset. It was detected that the young men are the main ones attacked with the vigorexia, they put women and older people can also be reached. Conclusion: Starting from the theoretical basement the present inquiries were formulated in this questionnaire that looks for to reach the indications that it predisposes the vigorexia, proposing a questionnaire that comes to identify possible upset related to the corporal dismorph trying with this auxiliary study in the detection of this syndrome that still lacks of many researches; to help this public that is formed by its majority of young academy visitors that you/they forget that the body is our main habitation